A High Performance Message-Passing System for Network of Workstations - Park, Sung-Yong; Hariri, Salim (The Journal of supercomputing, 1997)
With the proliferation of Network of Workstations (NOW) environment, there has been a great demand for a high performance message-passing system to implement High Performance Distributed Computing (HPDC) applications over NOW environment. NYNET (ATM wide area network testbed in New York state) Communication System (NCS) is a multithreaded message-passing system developed at Syracuse University that provides low-latency and high-throughput communication services over the Asynchronous Transfer Mode (ATM) based HPDC environment. NCS provides High Performance Application Communication Interface (HPI) to support applications that demand high-throughput and low-latency communication services. This paper outlines the general architecture of NCS and presents the implementation approach of NCS HPI over an ATM network. This interface has been developed by modifying Fore Systems' ATM Application Programming Interface (APt) and its device driver. NCS HPI uses read/write trap routines to bypass traditional operating system calls and kernel-level communication interface (e.g., UNIX System V Streams). It reduces latency, data transfer time, and avoid using traditional communication protocols (e.g., TCP/IP). This substantially improves the communication performance.